O signo como substituição: da semiótica de Peirce a uma teoria morfogenética do simbólico - António Machuco Rosa (2018)
In this article we analyze the definition of sign proposed by modern semiotic and semiological theories. Particular emphasis will be placed on the theory of Charles S. Peirce who, following a long tradition, defined the sign as a triadic structure in which the sign is in the place of something absent, the object, and determines an interpretant. It is held that in this theory, as in the proposed by Saussure, the definition of the sign as something that replaces an absent thing, its object, involves a circularity. We argue that this circularity can be avoided by using the morphogenetic theory of René Girard. It is shown how the hypothesis of the founding victim in Girard's theory allows to understand the emergence of the sign, and to reconstruct, without circularity, the basic structure of the sign in Peirce and Saussure. Finally, it is shown how the totality of symbolic systems can be derived from the original substitution present in the founding victim, highlighting the process of substitution present in the most universal form of human culture, the ritual of sacrifice.